BIOLOGICAL AND CHEMICAL CONTROL OF CINARA JUNIPERI (JUNIPER APHID) INFESTING JUNIPERUS VIRGINIANA (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This study provides a scientific analysis of biological and chemical control methods against Cinara juniperi, the main pest of Juniperus virginiana (Juniper aphid). The ecology of the pest, the damage it causes to trees, and the advantages and application methods of effective biological and chemical control measures are discussed in detail. The results highlight the importance of selecting environmentally safe and effective strategies for pest management, emphasizing the value of integrated approaches in controlling C. juniperi.
Keywords: Juniperus virginiana, Cinara juniperi, juniper aphid, biological control, chemical insecticides, pest management.